Integration of single photon emitters in 2D layered materials with a silicon nitride photonic chip - Frédéric Peyskens (Nature Portfolio, 2019)
Integration of photonic circuits with single photon emitters provides a promising route towards scalable quantum photonic chips. Here, the authors integrate a WSe2 monolayer onto a SiN chip and demonstrate the coupling of single photon emitters in WSe2 with the guided mode of a SiN waveguide.